Synthesis of BiOF/TiO2 Heterostructures and Their Enhanced Visible‐Light Photocatalytic Activity. Issue 3 (8th January 2020) - Nasr, Maryline; Huang, Wenshi; Bittencourt, Carla; Cui, Dandan; Sun, Ying; Wang, Lei; Caperaa, Nathalie Gaillard; Ning, Yuping; Song, Ping; Bonnet, Pierre; Wang, Cong
Abstract : Novel BiOF/TiO2 heterostructures with controlled amounts of BiOF and TiO2 have been successfully synthesized via a simple solid‐state sintering method. The structural, morphological and optical properties were analyzed using several characterization techniques. A shift of the TiO2 absorption edge toward the visible region was observed. The optimal molar ratio of BiOF/TiO2 was found to be (1:3) with a photodegradation percentage of 91.2 % and it was 7 and 5 times more efficient than that of pure BiOF or TiO2 nanopowder, respectively. BiOF/TiO2 (1:3) heterojunction has showed high photodegradation stability for the Rh B photodegradation after three cycles. In the proposed photocatalytic mechanism, TiO2 absorbed the visible light and carried out the photocatalytic reaction owing to the decrease of its band gap value due to the formation of oxygen vacancies, while BiOF played an important role in the charge separation process due to the intimate contact of the BiOF/TiO2 heterojunction. Abstract : The novel BiOF/TiO2 heterostructure with different molar ratio of BiOF and TiO2 were successfully elaborated via simple solid state sintering method. The optimal molar ratio of BiOF/TiO2 was found to be (1:3) with a photodegradation percentage of 91.2 % and it was 7 and 5 times more efficient than that of pure BiOF or TiO2 nanopowder, respectively.